Bibliometric Analysis of Rimbang (Solanum torvum) on Eye Health - Syaifullah, Annisa; Yuniarti, Elsa; Violita, Violita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Solanum torvum or takokak is one of the indigenous medicinal plants in Indonesia. Solanum torvum is part of the Solanaceae family or eggplant tribe. This plant contains carotenoids which have benefits for eye health. This study aims to analyze the scope of research on Solanum torvum on eye health. This research uses a qualitative descriptive method that refers to the literature (literature review) with the Scopus website. The data used for this study are articles in the 2015-2023 time span, totaling 263 articles. Data collection uses the keyword TITLE-ABS-KEY (solanum OR solanaceae OR eggplant AND eye OR vision). The application used for analysis is VOSviewer. The analysis used is co-occurance keyword analysis. In the network visualization, the most article publications in 2023 were 45 article publications. In the overlay visualization there is a large circle with cluster 1 there are keywords, adult, female, aged, and eye disease. In the density visualization there is the brightest color with the keywords female, adult, male, and human.